To the tub - Anderson, Peggy Perry (Boston : Houghton Mifflin Company, 1996)
Joe the frog needs a bath, but he makes the trip to the tub a challenge for his father.
Keywords: Frogs-Fiction; Baths-Fiction; Fathers and sons, Fiction